Study and implementation of drive test for development of long term evolution (LTE) network / Mohd Ezzuandi Ngadi - Ngadi, Mohd Ezzuandi (2015)
Drive Test is a method used by Radio Frequency (RF) Engineers to measure the quality of mobile radio network in open air interface. The requirement of Fourth Generation (4G) Long Term Evolution (LTE) as the latest technology in mobile network is far greater in term of data speed and it IP based technology makes it more challenge in voice services when synchronizing with previous technology. Circuit- Switched Fall Back (CSFB) is one of the services provide by the LTE technology in order to adapt with previous technology in voice services. This paper focuses on the idea of network optimization by collecting and analyzing the fourth generation LTE which include the drive test method on CSFB and Packet Switched (PS) services and analyzing the data using air interface post-processing NEMO Outdoor / Analyzer. This research has improved the mobile network performance with drive testing method by increasing the call setup rate and downlink throughput rate and decreasing the call drop rate.